2014
DOI: 10.1371/journal.pone.0111047
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Dynamic Optimal Design of Helical Vascular Graft for Stenotic Disturbed Flow

Abstract: Although a helical configuration of a prosthetic vascular graft appears to be clinically beneficial in suppressing thrombosis and intimal hyperplasia, an optimization of a helical design has yet to be achieved because of the lack of a detailed understanding on hemodynamic features in helical grafts and their fluid dynamic influences. In the present study, the swirling flow in a helical graft was hypothesized to have beneficial influences on a disturbed flow structure such as stenotic flow. The characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…stents, perfusion systems) that perturb flow profiles experienced by endothelial cells. Strutted stents or grafts are known to induce local disturbed flow that increases the risk of restenosis, thrombosis and neointimal hyperplasia (6), whereas flow helicity has been postulated to reduce flow disturbances and impede atheroprone flow signatures (7)(8)(9). Indeed, specific stents have been used to emulate physiological helical flows (7)(8)(9), and a recent clinical trial has demonstrated improved vessel patency, and therefore the clinical utility of reproducing helical SPF (10).…”
Section: Introductionmentioning
confidence: 99%
“…stents, perfusion systems) that perturb flow profiles experienced by endothelial cells. Strutted stents or grafts are known to induce local disturbed flow that increases the risk of restenosis, thrombosis and neointimal hyperplasia (6), whereas flow helicity has been postulated to reduce flow disturbances and impede atheroprone flow signatures (7)(8)(9). Indeed, specific stents have been used to emulate physiological helical flows (7)(8)(9), and a recent clinical trial has demonstrated improved vessel patency, and therefore the clinical utility of reproducing helical SPF (10).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from thermal [1] and chemical engineering [2] or medical applications [3] requirements, researches are conducted strongly related to process and phenomena optimization. A possibility for swirl flow development is described in the literature by using helical configurations [4]. The main advantage of this kind of geometries is the increase of particle mixing inside the specific zone associated for different applications or heat exchange efficiency, modifying the stagnation point or the particle residence time [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…A possibility for swirl flow development is described in the literature by using helical configurations [4]. The main advantage of this kind of geometries is the increase of particle mixing inside the specific zone associated for different applications or heat exchange efficiency, modifying the stagnation point or the particle residence time [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations